The implication on use of the "Easy Multiply Mind Method" in improving the level acquisition among Year 5 pupils / Shamsiah Othman - Othman, Shamsiah (2016)
Multiplication is one of the operations involve in the Mathematics syllabus in primary schools. However, the pupils’ main weakness is the difficulty in memorizing multiplication tables especially 6 to 8. The pupils have high tendency to forget the multiplication tables when they do not practise, memorise or apply it frequently. Most pupils memorize multiplication tables by mentalist way. Therefore, the “Easy Multiply Mind Method” is introduced. Besides that, this method can also be used to solve mathematical problems in multiplication operation when they have already mastered the method. The purpose of this research is to identify the effectiveness in improving the level of acquisition among Year 5 Pupils in Sekolah Kebangsaan Lumba Kuda Kuching, Sarawak to memorize multiplication tables in order to answer mathematical questions that consist of multiplications facts. This study is carried out in Sekolah Kebangsaan Lumba Kuda Kuching, Sarawak where all 38 selected respondents are from Year 5. The experiment begins by giving the pupils a pre-test before introducing the “Easy Multiply Mind Method” which consists of 15 multiplication questions involving tables 6 to 8 basic facts to review of mastery in basic multiplication facts and the pupils need to answer the questions in 10 minutes. To identify the effectiveness of the new method, the post-test is then distributed after teaching and exposing pupils to the “Easy Multiply Mind Method”. The result shows that the marks for post - test were much better than the pre-test. After the post - test, a set of questionnaires was administered to the same respondents to identify the effectiveness of this “Easy Multiply Mind Method” in solving mathematical problems. The research findings show pupils take a shorter time after using “Easy Multiply Mind method” in solving mathematical problems. They also find it easier to memorise multiplication tables 6 to 8 as compared to the conventional way. In conclusion, “Easy Multiply Mind Method” increases pupil’s achievement in mathematic under the topic of multiplication facts. Furthermore, using the “Easy Multiply Mind Method” can be one of the effective learning techniques for teaching and learning in the classroom.